Immunomodulation as Treatment for Severe Coronavirus Disease 2019: A Systematic Review of Current Modalities and Future Directions. (20th November 2020) - Meyerowitz, Eric A; Sen, Pritha; Schoenfeld, Sara R; Neilan, Tomas G; Frigault, Matthew J; Stone, John H; Kim, Arthur Y; Mansour, Michael K
Abstract: In severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, viral load peaks early and declines quickly after symptom onset. Severe coronavirus disease 2019 (COVID-19) is marked by aberrant innate and adaptive immune responses with an abnormal cytokine profile and multiorgan system dysfunction that persists well after viral clearance. A purely antiviral treatment strategy may therefore be insufficient, and antiviral agents have not shown a benefit later in the illness course. A number of immunomodulatory strategies are being tested, including corticosteroids, cytokine and anticytokine therapies, small molecule inhibitors, and cellular therapeutics. To date, the only drug to show a mortality benefit for COVID-19 in a randomized, controlled trial is dexamethasone. However, there remains uncertainty about which patients may benefit most and about longer-term complications, including secondary infections. Here, we review the immune dysregulation of severe COVID-19 and the existing data behind various immunomodulatory strategies, and we consider future directions of study. Abstract : Evidence supports an acute viral followed by an immune dysregulation phase in severe COVID-19 that is associated with inadequate early type I interferon response and imbalanced innate and adaptive immunity. We review clinical data available for various immunomodulatory therapies.